CT Derived Hounsfield Unit: An Easy Way to Determine Osteoporosis and Radiation Related Fracture Risk in Irradiated Patients - Yaprak, Gokhan; Gemici, Cengiz; Seseogullari, Ozgur O.; Karabag, Irem S.; Cini, Nilsu (Frontiers in Oncology, 2020)
Background: We aimed to evaluate osteoporosis, bone mineral density and fracture risk in irradiated patients by computerized tomography derived Hounsfield Units (HUs) calculated from radiation treatment planning system. Methods: Fifty-seven patients operated for gastric adenocarcinoma who received adjuvant abdominal radiotherapy were included in the study group. Thirty-four patients who were not irradiated after surgery comprised the control group. HUs of T12, L1, L2 vertebral bodies were measured from the computerized tomographies imported to the treatment planning system for all the patients. While the measurements were obtained just after surgery and one year later after surgery in the control group, the same measurements were obtained just before irradiation and one year after radiotherapy in the study group. Percent change in HU values (Δ%HU) was determined for each group. Vertebral compression fractures, which are the consequence of radiation induced osteoporosis and bone toxicity were assessed during follow-up. Results: There was no statistical significant difference in HU values measured for all the vertebrae between the study and the control group at the onset of the study. While HU values decreased significantly in the study group, there was no significant reduction in HU values in the control group after one year. significant correlation was found between Δ%HU and the radiation dose received by each vertebra. Insufficiency fractures (IFs) were observed only in the irradiated patients (4 out of 57 patients) with the cumulative incidence of 7 %. Conclusions: HU values are very valuable in determining bone mineral density and fracture risk. Radiation treatment planning system can be utilised to determine HU values. IFs are common after abdominal radiotherapy in patients with low vertebral HU values detected during radiation treatment planning. Radiation dose to the vertebral bones with low HU values should be limited below 20 Gy to prevent late radiation related bone toxicity.